A Study Of Employee Perception On TQM And Its Related Culture In Telekom Malaysia Perak - Abd. Rahman, Zainal Abidin (2000)
This research studied and analyzed the perception of the employees in Telekom Malaysia Perak regarding TQM implementation and its related cultures. Seven dimensions of TQM and five dimensions of cultures were evaluated using questionnaires that were sent